Identifikasi dan Kuantifikasi Manfaat Teknologi Informasi di Kabupaten Talaud - Bahar, Jasinda; Sentinuwo, Steven; Karouw, Stanley; Tuturoong, Nancy; Robot, Jimmy (Universitas Sam Ratulangi, 2020)
Talaud Regency has implemented information technology such to improve the performance of the officials as well as the quality of public services as a form of good governance. Presidential Instruction No 3 of 2003 concerning National Policy and Strategy on E-Government Development, and Presidential Regulation No 95 of 2018 on Electronic-based Government System, stated that, in order to have a clean, effective, transparent, and accountable governance along with quality and trustworthy public service, an electronic-based government system is needed.To understand the benefit of those information technology implementations in Talaud Regency Government, it is necessary to do a research and analysis. The data collecting technique was done by distributing questionnaires and doing interviews. using IT Valuation Matrix method to facilitate the research and analysis process. The research result shows that the information technology implementations in Talaud Regency have impacted positively because they are able to minimize the regional expenditure. It is also noted that the implementations have improved the performance of the officials and accelerate the government’s workflow despite of the inadequacy in infrastructure and human resource.